(untitled) (Papeles, 2022)
A modern and dynamic review of the National Constitution opens the door to the paradigm of the rights of nature in Argentina. It could be interpreted that they find their constitutional root in the implicit rights, in the duty to preserve biological diversity, in the reinterpretation of the word “inhabitant”, in the view of indigenous communities linked to the defense of mother earth or in the recognition of nature as an autonomous right made by the Inter,American Court of Human Rights.